Neuroprotective effects of essential oils in animal models of Alzheimer’s and Parkinson’s disease: a systematic review - Adrielle do Espírito Santos Macedo; Thayná Moraes Ferreira; Lane Viana Krejcová; Fernando Allan de Farias Rocha; Joyce Kelly R. da Silva; Laís Resque Russo Pedrosa; Bruno Duarte Gomes (PeerJ)
Essential oils (EOs), derived from aromatic plants, have garnered significant attention for their potential neuroprotective properties in neurodegenerative diseases. This systematic review evaluates recent advancements in understanding the neuroprotective role of EOs against Alzheimer’s disease (AD) and Parkinson’s disease (PD). Following PRISMA guidelines, we conducted a comprehensive literature search across three major databases (PubMed, Virtual Health Library, and Web of Science) from inception to January 2024, resulting in thirteen high-quality in vivo studies for qualitative analysis. The review assessed various EOs, with hydrodistillation being the predominant extraction method (66.66% of studies). Studies primarily utilized Wistar rats (46.15%) and various mouse strains, employing diverse disease induction methods including β-amyloid administration (30.7% of AD models), rotenone (7.7% of PD models), and 6-hydroxydopamine (7.7% of PD models). Administration routes varied, with oral administration being most common (38.4%), with gavage and inhalation each accounting for 23.1% of studies. Key findings revealed that EOs exhibit multifaceted neuroprotective mechanisms. In AD models (69.3% of studies), EOs reduced oxidative stress markers, decreased pro-inflammatory cytokine levels, and increased neuroprotective protein expression. In PD models (30.7% of studies), EOs demonstrated significant dopaminergic neuroprotection, with improvements in behavioral outcomes. Behavioral assessments showed consistent enhancements in memory, learning, and motor functions across studies. The systematic analysis provides compelling evidence for EOs’ neuroprotective efficacy, particularly in early-stage intervention. However, limitations include the predominance of animal studies, variability in dosing, and administration methods. The most promising EOs identified were from Pinus halepensis, Citrus limon, and Acorus species, showing particular efficacy in reducing cognitive deficits and oxidative stress. Chemical analysis revealed that compounds such as α-pinene, limonene, and β-caryophyllene were predominantly responsible for the observed therapeutic effects. The molecular mechanisms underlying these effects included modulation of cholinergic transmission, reduction of amyloid-β aggregation, and enhancement of antioxidant enzyme activities. These findings suggest that EOs could serve as valuable complementary therapeutic agents, particularly when standardized for specific bioactive compounds. Future research should focus on standardizing EO compositions, conducting human clinical trials to establish safety and efficacy profiles, and investigating potential synergistic effects with conventional treatments.